Alternative Management Practices for Water Conservation in Dryland Farming: A Case Study in Bijar, Iran - Sadegh-Zadeh, Fardin; Wahid, Samsuri Abd; Seh-Bardan, Bahi J.; Seh-Bardan, Espitman J.; Bah, Alagie (IntechOpen, 2011)
None